PEMBUATAN PROGRAM PERATAAN JARING GPS - Hutomo, Septiawan Setio; Awaluddin, Moehammad; Sabri, LM. (Jurnal Geodesi UNDIP, 2012)
In GPS surveying, GPS data processing is intended to calculate the coordinate of the points in a network based on observation data and get the coordinate of the observed points. In the measurement of control point network, to get the accurate coordinate, the first step is processing the baseline then followed by network adustment. Network adjusment is intended to make  the baseline that compose the network can be integrated correctly and consistently to get the coordinate of the observed points that is unique. Network adjusment generally use the least square adjustment method. Along with the progress in computers and programming, the calculation of the GPS network become more practical in its processing.   Gnet 1.0 applications using the windows programming language called Visual Basic 2008. This applications can automatically adjust the network using baseline data network.  The results of the Gnet 1.0 application compared with the results from Adjust and Sokkia Spectrum Survey show relatively similar results. It was concluded that the Gnet 1.0 application  can be used for GPS baselines network adjusment   Keywords : visual basic, GPS, baselines, least square adjustment.